STUDY OF AGING TEMPERATURE AND GRAIN ORIENTATION EFFECT ON MECHANICAL PROPERTIES OF 2014 AL ALLOY - TAUFIQ (NIM : 12506010), TANIA
Aluminum alloys are lightweight but strong material that is widely used for structural purposes, especially in the aerospace manufacturing industry. Lots of researches related to the strengthening of alloys 2xxx series have been done but still very little to discuss about the 2014 alloy, which of course have different strengthening properties. Al alloy 2014 is the second mostly used by PT. Dirgantara Indonesia as a framework for the Airbus aircraft type. The study was conducted to analyze the effect of grain orientation on the yield strength of alloy Al 2014 – related functions as a structure that has a specific assignment in their applications. The problems inherent in the industry is the length of time required for the natural aging process in 2014 alloys, which is around 96 hours, to achieve the optimum blend of strength values. Aging time can be shortened by increasing the aging temperature at a certain range. Research carried out by altering the temperature of aging, among others, at room temperature, 100 oC, 150 oC and 200 oC, and the hardness was measured every 4, 8, 12, 16, and 20 hours using a Vickers microhardness. Any variations will provide different nucleation speed, growth, and the strengthening of precipitates phases for a certain period. Microstructure was observed using optical microscope after the alloy is etched using Keller's reagent 3A. These microstructure changes are qualitative data to support changes in the value of hardness data against aging time. In this study also viewed the influence of alloy grain orientation with tensile loading in three different directions, namely: the longitudinal, long-transverse, and diagonal. Metallographic Tests were also performed to support the test results that showed the trend of violence against the length of time of aging. The results of experiments conducted concluded that increasing the aging temperature can accelerate the rate of precipitates nucleation and growth. This is indicated by the short time required to achieve optimum hardness of Al 2014 amounted to 118.4 HVN at a temperature of 150 oC that reached within 12 hours. This is in accordance with test results showing that the metallographic changes in precipitate’s cluster size do influenced the alloy strength. The value of hardness, yield strength and tensile strength (longitudinal direction) 2014 aluminum alloy at the aging temperature of 150oC for 12 hours (optimum conditions) are respectively 118.4 HVN; 349.11 MPa, and 232.89 MPa.